Black hole Cosmos and the Micro Cosmos - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2013)
Point of ‘big bang’ can be considered as the center or characteristic reference point of cosmic expansion in all directions. If so, the existence of ‘preferred direction’ in the universe may not be wrong. In this paper by considering the previously proposed concepts of black hole cosmology, independent of quantum mechanics an attempt is made to fit the fine structure ratio and CMBR wavelength. It can be suggested that, 'hbar' can be considered as a cosmological increasing atomic variable related to the revolving electron’s angular momentum and 'h' can be considered as a cosmological constant related to electromagnetic and thermal energy. If one is able to express the Wien’s displacement constant in terms of electric charge and thermal energy constant, then automatically 'hc' can be shown to be a cosmological constant related to electromagnetic and thermal energy and with this idea the Planck’s quantum nature of energy can also be understood. With the discovered applications it is very clear to say that, without a joint and unified study of cosmology and atomic & particle physics, one should not deny the concepts of black hole cosmology. Independent of the redshift observations and considering the proposed relations, with a great confidence now one can start seeing/observing the universe as a primordial expanding and light speed rotating black hole. Based on the proposed relations and concepts of black hole cosmology, definitions of cosmic homogeneity and cosmic isotropy must be re-addressed. It is also clear that, now the black hole universe is expanding in a decelerating mode at a very small rate in such a way that with current technology one cannot measure its deceleration rate. Finally it can be suggested that cosmic acceleration and dark energy can be considered as pure mathematical concepts and there exists no physical base behind their affirmation. For the most serious cosmologists this may be a bitter news, but it is a fact. Authors hope that, by 2015 definitely this subject will come into main stream physics.